Legal Analysis Of Land Dispute Settlement In Tlogoretno Village Based On Restorative Justice - M. Yanto; khitam, Muhammad chusnul; Wulandari, Rosy Dwi (Jurnal Independent, 2024)
ABSTRACT Land disputes in Indonesia, including in Tlogoreto Village, are complex and often protracted problems when resolved through conventional litigation. The lengthy and costly legal process makes alternative approaches, such as Restorative Justice, an increasingly relevant solution. Restorative Justice emphasizes the restoration of relations between the parties to the dispute through dialogue and mutual agreement. In this context, the restorative approach is expected to be able to provide a more effective and harmonious settlement of land disputes in Tlogoreto Village. This study uses a normative juridical method with an analysis of applicable laws and regulations, as well as legal doctrines related to land dispute resolution and the application of Restorative Justice. The Restorative Justice approach in resolving land disputes in Tlogoreto Village focuses on mediation involving all parties to the dispute, as well as community leaders as mediators. This process aims to reach a fair agreement for all parties, by prioritizing the restoration of social relations. The analysis shows that the application of Restorative Justice is more effective in reducing tensions and producing sustainable solutions than resolving disputes through the courts. However, the challenge in applying this method lies in the lack of public understanding of Restorative Justice and the limited formal recognition of the results. Restorative Justice offers an alternative to resolving land disputes that is faster, cheaper, and able to improve relations between the parties to the dispute in Tlogoreto Village. This approach is in line with the principle of restorative justice which focuses on recovery rather than punishment. Although its application has not yet been fully formally recognized in Indonesia's legal system, Restorative Justice can be an important step in land dispute settlement reform, especially at the local level.